A modified Poisson-Boltzmann approach to homogeneous ionic solutions - Outhwaite, C.W. (Condensed Matter Physics, 2004)
The mean electrostatic potential approach to ionic solutions was initiated by the mean field work of Gouy and Chapman for inhomogeneous systems, and Debye and Huckel for bulk solutions. Any successful extension of the mean field theories requires an adequate treatment of both the exclusion volume and fluctuation terms. One such development has been the modified Poisson-Boltzmann approach. Although the bulk modified PoissonBoltzmann theory was introduced 35 years ago, only a limited amount of work has been put into its development due to the successful application of liquid state theories to ionic systems. We outline here the bulk modifi ed Poisson-Boltzmann equation, comment on some of its successes, and mention some outstanding problems.